REVIEW OF AYURVEDIC STRATEGIES TO OVERCOME ATINIDRA (HYPERSOMNIA) AND IMPROVE QUALITY OF LIFE - Prajapati Vikas; Sabarwal Gunjan; Panda SriKanta Kumar (International Journal of Applied Ayurved Research, 2020)
Sleep is one of the trayopstambha (Subpillars) mentioned in Ayurveda. It plays an important role in proper brain function and systemic physiology across many body systems. In present era sleep problems are increasing including excess in quantity of sleep. Many factors are responsible for this ranging from environmental factors, lifestyles, medical condition etc. which has both short- and long-term adverse effect on health. Many research have been done on sleep disorders and researchers have shown that hypersomnia causes more complication and has increased mortality rate as compared to insomnia. Many solutions are there for insomnia and persons suffering from this consider it as a problem but a hypersomnia patient does not consider it until it causes some health complication. Thus, an Ayurvedic literature review was done to know the etio-pathogenesis of atinidra and probable preventive & curative measures to overcome this and improve the quality of life as Atinidra can be managed well by Ayurvedic principles which not only includes treatment but dietary and lifestyle modifications as well. Further, there is no mention of any single or poly herb formulation which can prove to be effective in atinidra, so it is need of an hour to do research in this area.